2017
DOI: 10.15517/rbt.v66i1.30269
|View full text |Cite
|
Sign up to set email alerts
|

Gremios y diversidad de hormigas (Hymenoptera: Formicidae) en tres usos del suelo de un paisaje cafetero del Cauca-Colombia.

Abstract: Guilds and diversity of ants in three land uses from a coffee landscape at Cauca -Colombia. In the last 50 years, Colombian coffee production has undergone a great transformation from traditional plantations grown below the forest's shade, to vast extensions of coffee plantations consisting of free exposition to sun. These systems reduce native biodiversity and its associated ecosystem services. Simultaneously, shaded coffee plantations operate as potential shelter of such biodiversity, favoring its dispersal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Our results are consistent with previous findings indicating that limited nesting resources after the conversion of natural forest to monoculture plantations reduces ant abundance and TD (Armbrecht et al ., 2004; Philpott & Foster, 2005; Arenas‐Clavijo & Armbrecht, 2018; Ibarra‐Isassi et al ., 2021). Analysis of ant FD and PD indicated that the loss of species richness in rubber plantation was not random and that the simplified ant communities with limited nesting resources could have negative effects on ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with previous findings indicating that limited nesting resources after the conversion of natural forest to monoculture plantations reduces ant abundance and TD (Armbrecht et al ., 2004; Philpott & Foster, 2005; Arenas‐Clavijo & Armbrecht, 2018; Ibarra‐Isassi et al ., 2021). Analysis of ant FD and PD indicated that the loss of species richness in rubber plantation was not random and that the simplified ant communities with limited nesting resources could have negative effects on ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The Cauca region is in the Colombian massif of the Popayán plateau with sun and shade coffee crops in an agroforestry mosaic, with mixed and forestry crops, small fragments of forest and riparian forests (Criollo and Bastidas, 2011;Arenas-Clavijo and Armbrecht, 2018). Although the coffee landscape is increasing in agricultural intensity, to the detriment of biodiversity (Armbrecht, 2003;Philpott et al, 2008;Harvey et al, 2021), it continues to host more diversity as an agroecosystem (Letourneau et al, 2011) than extensive monocultures such as the sugar cane and cattle ranching model in the Valle del Cauca department to the north (Marull et al, 2018;Sardi et al, 2018).…”
Section: Study Sitesmentioning
confidence: 99%
“…El fragmento de bosque y la matriz son sitios parecidos en cuanto a su composición de hormigas, posiblemente por la dominancia de especies generalistas, que ingresan desde el pastizal a usos de suelo con presencia de árboles [34], los cuales les proveen diferentes sitios de nidificación [28], así mismo las especies generalistas tienen una mayor tasa de colonización de fragmentos pequeños [35]. La similaridad en la composición probablemente también se presentó, porque la matriz puede influir lo que sucede en los trero hallaron que al aumentar la temperatura incrementó la riqueza de hormigas, sin embargo, en el fragmento de bosque evidenciaron que la riqueza disminuyó a medida que la temperatura aumentó; según los autores, esto se explica porque las hormigas bajo estas condiciones forrajean más y obtienen mayor energía [39] y en los meses más cálidos la disponibilidad de alimentos es mayor [32], en cambio, Moreno et al [37] mencionan que las especies son típicas a las condiciones ambientales del sitio.…”
Section: Grupo Dosunclassified